2013
DOI: 10.1371/journal.pone.0063834
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Nodule with Benign Cytology: Is Clinical Follow-Up Enough?

Abstract: ObjectiveIn this multicenter study, we investigated the management algorithm for thyroid nodules with benign cytology using US features from data collected from 7 institutions.Materials and MethodsThe institutional review board approved this retrospective study. Data on 700 focal thyroid nodules in 673 consecutive patients were collected from 7 university-affiliated hospitals. This study included nodules that were diagnosed as benign at initial cytologic evaluation and that underwent pathologic or follow-up st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
5
9
0
Order By: Relevance
“…Interestingly, a very high cancer rate (32 %) was found. This finding was perfectly in agreement with that previous reported by papers analyzing the likelihood for malignancy in these specific nodules [46][47][48]. More recently, CNB or conventional FNAC was proposed to patients with newly discovered at risk thyroid lesions [24]; the diagnostic accuracy of CNB was significantly higher than that of FNAC [24].…”
Section: Use Of Cnb In Thyroid Neoplasms (Thy 3/class 3/category Iii-supporting
confidence: 91%
“…Interestingly, a very high cancer rate (32 %) was found. This finding was perfectly in agreement with that previous reported by papers analyzing the likelihood for malignancy in these specific nodules [46][47][48]. More recently, CNB or conventional FNAC was proposed to patients with newly discovered at risk thyroid lesions [24]; the diagnostic accuracy of CNB was significantly higher than that of FNAC [24].…”
Section: Use Of Cnb In Thyroid Neoplasms (Thy 3/class 3/category Iii-supporting
confidence: 91%
“…The 15.8 % rate of malignancy identified in our specific series is substantially higher than that predicted by Bethesda and ATA guidelines for benign USFNAs. Yet, it is consistent with the higher rates reported throughout literature, reaching values as high as 24.2 % [ 2 , 5 , 10 12 ]. This wide range may be explained in part by variations in technique, expertise and subjective interpreting differences between pathologists reading the slides and physicians performing ultrasounds and USFNAs in different institutions.…”
Section: Discussionsupporting
confidence: 92%
“…A study by Rosário and Purisch consisting of 895 nodules put in evidence that the repetition of FNA is useful in detecting false-negative cases, when the nodule shows characteristics of malignancy at ultrasound rather than when it grows [ 12 ]. This concept was more recently confirmed by a multicentre study stating that evaluating 700 nodules initially diagnosed as benign showed that false-negative results were found in 1–3% of cases (depending on the centre) and that the likelihood of a cytologically benign nodule with suspicious US characteristics being malignant was higher than that of one without suspicious US (4.7% versus 0.8%; P < 0.05) [ 13 ]. The same low rate of false-negative FNA was demonstrated by the studies by Torre and Oertel, while we have to be reminded that, in about 2/3 of cases, false-negative results pertain to nodules larger than 30 mm [ 14 16 ].…”
Section: Discussionmentioning
confidence: 95%